2017
DOI: 10.1371/journal.pone.0171903
|View full text |Cite
|
Sign up to set email alerts
|

Inactivity/sleep in two wild free-roaming African elephant matriarchs – Does large body size make elephants the shortest mammalian sleepers?

Abstract: The current study provides details of sleep (or inactivity) in two wild, free-roaming African elephant matriarchs studied in their natural habitat with remote monitoring using an actiwatch subcutaneously implanted in the trunk, a standard elephant collar equipped with a GPS system and gyroscope, and a portable weather station. We found that these two elephants were polyphasic sleepers, had an average daily total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
90
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(101 citation statements)
references
References 58 publications
9
90
1
1
Order By: Relevance
“…Table gives an overview on the literature of quantitative studies on elephant resting and sleeping behavior under free‐ranging and different captive conditions. For the African species, daily lying rest durations have been identified in two adult females, while such quantitative results from the wild are lacking for the Asian species (Gravett et al, ). In the wild, African elephants have been observed to go for up to 9 days without lying down to sleep (Paul Manger, personal communication).…”
Section: Resultsmentioning
confidence: 99%
“…Table gives an overview on the literature of quantitative studies on elephant resting and sleeping behavior under free‐ranging and different captive conditions. For the African species, daily lying rest durations have been identified in two adult females, while such quantitative results from the wild are lacking for the Asian species (Gravett et al, ). In the wild, African elephants have been observed to go for up to 9 days without lying down to sleep (Paul Manger, personal communication).…”
Section: Resultsmentioning
confidence: 99%
“…The correlation to natural light conditions may be species‐specific, and as such further studies are required. Gravett et al () showed that light and sunset played no significant role in sleep onset in African elephants, but that environmental conditions (ambient air temperature, relative humidity) had a larger impact. Many ecological factors influence the frequency and duration of sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Absence of movement is therefore routinely used as a proxy to measure sleep across a wide range of animals, spanning from jellyfish to elephants (16,24,25). In Drosophila too, sleep can be estimated by measuring the absence of walking bouts, generally using a commercially available device to detect whenever an isolated fly crosses the midline of a tube (26).…”
Section: Virtually Sleepless Flies Are Found In a Non-mutant Populationmentioning
confidence: 99%
“…We know that some species -such as elephants (16) or giraffes (17) -have evolved to cope with limited amount of sleep and several genetic mutations conferring short sleeping phenotypes in flies, rodents, and humans have been characterised in the past two decades (reviewed in (18)); some animals are also able to forego sleep for days or weeks in particular ecological conditions (16,(19)(20)(21), but the identification of a constantly sleepless animal can be considered a holy grail of the field.…”
Section: Introductionmentioning
confidence: 99%